Analisis Kebutuhan Air dan Nutrisi AB MIX untuk Pertumbuhan Tanaman Kangkung Hidroponik di Desa Mungguk Kecamatan Sekadau Hilir Kabupaten Sekadau - Erwin (Hunatech Vol. XXX, No. XXX, 2025)
Mungguk Village is a small village located in Sekadau Regency. With a population of 9,315 people consisting of 4,787 men and 4,528 women, this is certainly not a small number. Seeing these numbers and information makes us want to help the community in the agricultural sector, it is hoped that this research can help housewives and people who want to utilize narrow land in their yards as agricultural land. This study aims to determine the water and nutrient needs of AB Mix for hydroponic kale plants. The average water requirement for hydroponic kale plants with ideal growth during growth requires 104 ml-110 ml of water/plant, P3 uses up 0.83 ml of nutrients/plant. The difference in dosage greatly affects the growth and shoots of plants, which greatly affects the production of kale plants. The more shoots the better because it will have an impact on the harvest.